Dukungan kepada Kader Posyandu untuk Melakukan Pemeriksaan Payudara Sendiri Guna Mendeteksi Dini Kanker Payudara - M Pandawa, Rugaya; Fatmah M. Saleh; Nuzliati T. Djama (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2024)
One of the non-communicable diseases that is a burden on health worldwide is cancer. The purpose is to improve the knowledge and skills of Posyandu cadres for early detection of breast cancer through breast self-examination. The Posyandu cadre training began with a pre-test for the cadre's knowledge about early detection of breast cancer and the results showed that most of them had insufficient knowledge (90%) and sufficient (10%). Community service workers provided cadre training materials, mentoring 15 cadres from three Posyandus monthly, and educated mothers and women of childbearing age about early detection of breast cancer through BSE. The results of the community service showed that there was an increase in the knowledge of Posyandu cadres about efforts to detect early breast cancer through the SADARI program. As a result, the cadres' knowledge increased according to the target of up to 90%. Meanwhile, for the skills of the cadres, an increase of up to 90% was seen in the six months. In conclusion, partner investment in the form of materials and training has had a positive impact on increasing the knowledge and skills of posyandu cadres in early detection of breast cancer through the BSE program